Chapter Note alla traduzione - Chiarini, Elena (Studi di Traduzione Letteraria Lusofona, 2020)
The Italian translation of the literary work of Adalberto Alves A presença dos dias / La presenza dei giorni is accompained by some usuful translation notes edited by Elena Chiarini in this volume.